Association of Serum Testosterone with Various Severity of Acne Vulgaris in Adult Women - Umi Miranti; Diah Mira Indramaya; Hari Sukanto (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2017)
Background: Acne Vulgaris (AV) is a chronic and obstructive inflammatory skin disease of the pilosebaceous unit. Testosterone is main androgen hormone that have a role in the pathogenesis of AV. Pevious researches have shown controversial results regarding serum testosterone levels in AV. Purpose: To evaluate the association of serum testosterone levels with AV severity in adult women in Dermatovenereology Outpatient Clinic of Dr. Soetomo General Hospital Surabaya. Methods: This is an analitic observational study, with 37 patients based on the inclusion and exclusion criteria. Results: Mean serum testosterone level in mild AV group was 39.16 + 24.18µg/dL, moderate AV group was 39.75 + 23.75 µg/dL, and severe AV group was 52.46 + 24.00 µg/dL. These results indicate that serum testosterone level in severe AV group was higher than moderate and mild AV groups. But there was no statistically significant correlation between serum testosterone levels and the severity of AV. Conclusions: Serum testosterone levels in patients with severe AV was higher than moderate and mild AV. No correlation between serum testosterone levels with AV severity in adult women. Further research ruled out confounding factors is needed to determine hormonal role in the pathogenesis of AV.